Caribbean Business Cycles - Cashin, Paul (IMF Working Papers; Working Paper ;, 2004)
This paper identifies and describes key features of Caribbean business cycles during the period 1963-2003. In particular, the chronologies in the Caribbean classical cycle (expansions and contractions in the level of output) and growth cycle (periods of above-trend and below-trend rates of economic growth) are identified. It is found that Caribbean classical cycles are longer-lived than those of developed countries and non-Caribbean developing countries. While there are large asymmetries in the duration and amplitude of phases in the Caribbean classical cycle, on both measures the Caribbean growth cycle is much more symmetric. Further, there is some evidence of synchronization among the classical cycles of Caribbean countries, and stronger evidence of synchronization of Caribbean growth cycles.